2012
DOI: 10.1007/s00439-012-1174-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of polymorphisms associated with cytokine responses in smallpox vaccine recipients

Abstract: The role that genetics plays in response to infection or disease is becoming increasingly clear as we learn more about immunogenetics and host-pathogen interactions. Here we report a genome-wide analysis of the effects of host genetic variation on cytokine responses to vaccinia virus stimulation in smallpox vaccine recipients. Our data show that vaccinia stimulation of immune individuals results in secretion of inflammatory and Th1 cytokines. We identified multiple SNPs significantly associated with variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 64 publications
1
70
0
Order By: Relevance
“…Rs6813517 is located at 367 kilobase from SPOCK3 , encoding a member of a novel family of calcium-binding proteoglycan proteins, which is strongly expressed in cerebral cortex and hippocampus. Another variant near SPOCK3 (rs13111850, R 2 = .003 with rs6813517) was recently found to be associated with variations in cytokine secretion in response to smallpox vaccine (34). Interestingly, an immune system dysfunction has been suggested in AD based on findings from recent AD GWAS and genome-wide pathway analyses (19,3537).…”
Section: Discussionmentioning
confidence: 99%
“…Rs6813517 is located at 367 kilobase from SPOCK3 , encoding a member of a novel family of calcium-binding proteoglycan proteins, which is strongly expressed in cerebral cortex and hippocampus. Another variant near SPOCK3 (rs13111850, R 2 = .003 with rs6813517) was recently found to be associated with variations in cytokine secretion in response to smallpox vaccine (34). Interestingly, an immune system dysfunction has been suggested in AD based on findings from recent AD GWAS and genome-wide pathway analyses (19,3537).…”
Section: Discussionmentioning
confidence: 99%
“…The phenotype of interest is vaccinia virus-induced IFN-a production detected in peripheral blood mononuclear cells (PBMCs) from first-time recipients of smallpox vaccine. More details about the study cohorts can be found in Ovsyannikova et al (2011Ovsyannikova et al ( , 2012Ovsyannikova et al ( , 2014 and Kennedy et al (2012) gender, time from immunization to blood draw, vaccination date, immune assay batch, and the first principal component to adjust for potential population stratification. For the San Diego cohort, the phenotype was regressed on the following covariates: date of IFN-a assay, date of blood draw, shipping temperature of the sample, site the sample was drawn from, and the second principal component (the first is not included because it is not significant).…”
Section: Application Of Methodsmentioning
confidence: 99%
“…(3) This observation might also be because of chance or an unknown biological mechanism. For instance, a GWAS (Kennedy et al, 2012) showed that MAMLD1, 586 kb upstream from the deletion, was associated with immune response to smallpox vaccine; the gamma-aminobutyric acid receptor subunit gene, GABRE, is 851 kb downstream from the deletion.…”
Section: Discussionmentioning
confidence: 99%